EDUCATING THE DEVELOPING MIND A Developmental Theory of Instruction - Demetriou, Andreas; Spanoudis, George; Greiff, Samuel; Panaoura, Rita; Vainikainen, Mari-Pauliina; Kazi, Smaragda; Makris, Nikolaos (Routledge, Taylor & Francis Group, 2024)
A must read for anyone working within education or intellectual development, Educating the Developing Mind introduces and integrates classical and modern research with the theory of the developing mind, creating a robust theory of learning and instruction. Drawing on the theories of Piaget, Bruner and Vygotsky, coupled with 40 years of empirical research, this book highlights the importance of individual and social construction in learning and proposes a robust framework and methodology for teaching and strengthening learner cognitive processes. Drawing on subject-specific research, this essential book highlights how cognitive development takes place and advocates a guided constructive approach to teaching. Topics explored span from the individual learner to the wider educational community, including but not limited to: Development of the mind Personality and individuality The brain Predicting school performance Measuring and improving intelligence Problem solving skills Language This is an essential read for anyone working within education who wants to better understand the cognitive processes involved in the developing mind and to improve learning and instruction within their school, college or university.